Literature Review: Risiko Bahaya K3 Pada Kapal dan Nelayan - Syaibah Nasution, Nadia; Susilawati, Susilawati (PT. Alahyan Publisher Sukabumi, 2024)
The risk of K3 hazards in shipping is a problem that bothers fishermen, be it physical, chemical, biological, ergonomic and psychological factors. The purpose of this research is to find out what K3 hazard risks exist on ships and are experienced by fishermen. This research method was carried out by analyzing 5 journals that were obtained in accordance with the criteria. The results of this review found that the risk of K3 hazards on boats and fishermen was decompression, fire, noise, punctures and cuts, and slippery floors.